2004
DOI: 10.1111/j.0038-4941.2004.08502005.x
|View full text |Cite
|
Sign up to set email alerts
|

The Context for Political Corruption: A Cross‐National Analysis*

Abstract: Objective. How do we explain variations across nations in the incidence of political corruption? Recent theoretical work locates the causes for corruption in a combination of institutional conditions: monopoly power, little accountability, and wide discretion. This focus on the form of political institutions clarifies the microscale causes of political corruption, but it leaves unanswered questions about the macro-scale causes of corruption. Methods. This article addresses these questions about the macro scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 31 publications
1
61
0
1
Order By: Relevance
“…Nye (1967), for example, defines corruption as ''behavior which deviates from the formal duties of a public role because of private-regarding pecuniary or status gains.' ' Todaro and Smith (2014), on the other hand, describe corruption more generally as ''the abuse of public trust for private gain'' that is likely to appear where there is a distinct lack of trust between governmental officials and the public (Xin and Rudel 2004). Eiras (2003) in turn maintains that corruption is a ''form of unethical behavior or wrongdoing,'' where unethical behavior refers to a social consensus that these actions are bad.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nye (1967), for example, defines corruption as ''behavior which deviates from the formal duties of a public role because of private-regarding pecuniary or status gains.' ' Todaro and Smith (2014), on the other hand, describe corruption more generally as ''the abuse of public trust for private gain'' that is likely to appear where there is a distinct lack of trust between governmental officials and the public (Xin and Rudel 2004). Eiras (2003) in turn maintains that corruption is a ''form of unethical behavior or wrongdoing,'' where unethical behavior refers to a social consensus that these actions are bad.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many scholars who study this relationship have concluded that corruption or perceived government corruption, by and large, has a corrosive impact on political trust among the general public (Citrin and Luks 2001;Pharr 2000;anderson and Tverdova 2003;della Porta 2000;Miller and Listhaug 1999;Chang and Chu 2006;Mishler and Rose 1997;Seligson 2002). other studies show that a lack of either interpersonal or political trust leads to higher levels of corruptive behavior or perceptions of corruption (heidenheimer 1996; Xin and Rudel 2004;Cleary and Stokes 2006). Stephen Morris and Joseph Klesner (2010) demonstrate, in their case study of Mexico, a strong, mutual causal relationship between perceptions of corruption and trust in political institutions.…”
Section: Perceived Government Corruptionmentioning
confidence: 99%
“…More trusting individuals, in short, may be quicker to condemn the corrupt conduct they find around them. There may also be a powerful interactive effect here whereby trust not only influences the perception of corruption (LaPorta, Lopez‐De Silanes, Hleifer and Ishny, 1997; Xin and Rudel, 2004), but corruption also undermines trust (Rothstein and Stolle, 2002).…”
Section: Participation and Perceptions At The Individual‐level: The Cmentioning
confidence: 99%